Kajian Fitokimia dan Potensi Bioaktif Jahe (Zingiber Officinale Rosc.) sebagai Minuman Fungsional Peningkat Metabolisme - Aisha Noviadiyanti; Ardi mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Ginger (Zingiber officinale Rosc.) is a spice plant with significant potential for the development of natural-based functional foods, particularly as a metabolism-enhancing beverage. The traditional use of ginger as a health drink highlights the need for scientific studies to strengthen evidence of its physiological benefits. This article aims to review the phytochemical composition of ginger rhizomes and their bioactive potential as a functional beverage for improving metabolic function. The research employed a qualitative approach with descriptive analysis based on a literature review of relevant national and international scientific publications. The discussion reveals that ginger rhizomes contain various phytochemical compounds, including gingerol, shogaol, zingerone, essential oils, flavonoids, alkaloids, saponins, triterpenoids, and dietary fiber, which exhibit thermogenic, antioxidant, anti-inflammatory, and metabolic regulatory activities. These bioactive compounds act synergistically to enhance energy expenditure, metabolic efficiency, and overall metabolic balance. The formulation of ginger as a functional beverage enables improved bioavailability of active compounds while offering high consumer acceptance and safety for regular consumption. Based on the findings, ginger demonstrates strong potential as a nutraceutical-based functional drink that supports metabolic enhancement and long-term metabolic health